Peran Supervisi Kepala Sekolah dalam Menciptakan Lingkungan Belajar yang Inovatif: Tinjauan Literatur Sistematik - Tetri Hariyanti (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to describe and analyze the role of principal supervision in creating an innovative learning environment in schools. Effective supervision serves not only as a monitoring tool but also as a means of fostering and developing teacher professionalism. Principals play a strategic role in fostering a culture of innovation through a participatory, collaborative, and sustainable supervisory approach. This study employed a qualitative approach with data collection techniques including interviews, observations, and documentation studies. The results indicate that structured supervision oriented toward improving the quality of learning can encourage teachers to develop creative and relevant learning methods that meet students’ needs. Furthermore, principal support in the form of training, provision of facilities, and the creation of a positive work climate are key supporting factors in building an innovative learning environment. Thus, principal supervision plays a vital role in creating a school culture that is progressive and adaptive to change.